Moringa leaf tea as an antihyperglycemic alternative of type 2 diabetes mellitus in the elderly - Prasetya, Fika Indah; Haryanti, Eka; Lie, Sukirman; Sulastri, Afianti; Sumartini, Sri; Astuti, Novia Dwi; Jubaedah, Ade; Anggraeni, Surti; Sasmito, Priyo (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia due to insulin resistance or decreased insulin secretion. Herbal complementary therapies are increasingly in demand as an alternative to managing blood sugar levels. However, studies of its effectiveness as a single therapy in the elderly have not been widely researched. Purpose: To evaluate the effectiveness of moringa leaf tea as an antihyperglycemic alternative in elderly patients with type 2 diabetes mellitus. Method: A case report study conducted on one participant to evaluate the effect of moringa leaf tea on fasting blood sugar levels in elderly people with type 2 Diabetes Mellitus (DM). This approach was chosen to document individual responses to herbal interventions in actual clinical conditions and provide an in-depth picture of changes in blood sugar levels after intervention. The patient in this study was a 61-year-old woman who had been diagnosed with type 2 DM for one year and was not taking antihyperglycemic drugs. The participant had a history of non-compliance with pharmacological therapy due to previously felt side effects. Results: Before the intervention, the patient reported experiencing typical symptoms of hyperglycemia, such as frequent thirst, increased urination frequency especially at night, and fatigue that interfered with daily activities. Blood sugar levels were measured before the intervention, and were found to be 256 mg/dL, indicating hyperglycemia. After consuming moringa leaf tea 3 times a day for three consecutive days, blood sugar levels decreased and on the 3rd day it was 220 mg/dL. In addition, the patient also reported improvements in clinical symptoms, such as reduced thirst, increased urination frequency especially at night, and increased energy. Conclusion: Consumption of Moringa leaf tea can lower blood sugar levels in elderly people with type 2 diabetes mellitus without antidiabetic drugs. In addition, improvements in clinical symptoms such as reduced thirst, urination frequency, and increased energy were also observed. Suggestion: Further studies are needed with larger samples and longer intervention periods to evaluate its long-term efficacy and safety. In addition, this study can explore more deeply the molecular mechanisms associated with the antihyperglycemic effects of Moringa leaves and its potential in natural therapy-based diabetes management strategies.